2020
DOI: 10.21203/rs.3.rs-55365/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Current situation of medication errors in Saudi Arabia: a nationwide observational study

Abstract: BackgroundMedication process complexity could cause confusion among healthcare professionals (HCPs) and patients and lead to medication errors. This nationwide study aimed to characterize the types of medication errors and determine the error occurs in different stages of the medication process.MethodsThis was a retrospective observational study of medication errors reported by 265 government hospitals and primary care centers during the period of March 2018 to June 2019. The reported information include sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Some scheduled shifts that may last longer than 8 or even 12 hours may not follow the traditional pattern of the day, evening, and night shifts [19]. Several studies showed the quantity of MEs being still high [22][23][24]. A study shows that nurses spend almost 45% of their work time performing medication therapy, with studies confirming that 59%-78% of MEs are associated with hospital staff nurses [23][24][25][26].…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scheduled shifts that may last longer than 8 or even 12 hours may not follow the traditional pattern of the day, evening, and night shifts [19]. Several studies showed the quantity of MEs being still high [22][23][24]. A study shows that nurses spend almost 45% of their work time performing medication therapy, with studies confirming that 59%-78% of MEs are associated with hospital staff nurses [23][24][25][26].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Several studies showed the quantity of MEs being still high [22][23][24]. A study shows that nurses spend almost 45% of their work time performing medication therapy, with studies confirming that 59%-78% of MEs are associated with hospital staff nurses [23][24][25][26]. A Swedish study identified that almost 45% of MEs rates are related to wrong dosage and other errors [27].…”
Section: Background and Related Workmentioning
confidence: 99%